2008
DOI: 10.1088/0953-2048/22/1/015019
|View full text |Cite
|
Sign up to set email alerts
|

Structural and critical current properties in polycrystalline SmFeAsO1−xFx

Abstract: A series of polycrystalline SmFeAsO 1-x F x bulks (x=0.15, 0.2, 0.3 and 0.4) were prepared by a conventional solid state reaction. Resistivity, susceptibility, magnetic hysteresis, critical current density and microstructure of these samples have been investigated. The resistivity result shows that critical transition temperature Tc increases steadily with increasing fluorine content, with the highest onset Tc=53 K at x=0.4. On the other hand, a study on the effect of lattice constants on critical transition t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
41
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 17 publications
5
41
0
Order By: Relevance
“…Similar to the cuprates, the Fe-As layer is thought to be responsible for superconductivity and La-O layer is carrier reservoir layer to provide electron carrier. By replacing La with other rare earths, T c can be raised to above 50 K [2][3][4][5][6][7]. Late on, the oxygen-free iron arsenide compounds AFe 2 As 2 (denoted as FeAs-122) were discovered and superconductivity was found by appropriate substitution or under pressure [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the cuprates, the Fe-As layer is thought to be responsible for superconductivity and La-O layer is carrier reservoir layer to provide electron carrier. By replacing La with other rare earths, T c can be raised to above 50 K [2][3][4][5][6][7]. Late on, the oxygen-free iron arsenide compounds AFe 2 As 2 (denoted as FeAs-122) were discovered and superconductivity was found by appropriate substitution or under pressure [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of superconductivity in Fe-As based compounds, with a critical transition temperature as high as 55 K, has sparked enormous research effort to understand its structure-property relationships [1][2][3][4][5][6]. One aspect of Fe-As based superconductors that has particular technological importance is that the grain boundaries in bicrystals do not appear to lower the overall critical current (J c ) as heavily as YBa 2 Cu 3 O 1-δ [7,8].…”
mentioning
confidence: 99%
“…One aspect of Fe-As based superconductors that has particular technological importance is that the grain boundaries in bicrystals do not appear to lower the overall critical current (J c ) as heavily as YBa 2 Cu 3 O 1-δ [7,8]. A remarkable transport inter-grain J c of ~10 5 A/cm 2 at 4 K and self field has been reported in [001]-tilt cobalt-doped BaFe 2 As 2 bicrystals with a high misorientation angle of 45 o [8], offering the possibility of a number of industrial applications. This is in contrast to polycrystalline samples, which show a relative low inter-grain (transport) J c of ~10 3 A/cm 2 at 4.2 K and self field [3][4][5]9].…”
mentioning
confidence: 99%
“…In addition to T c , these iron based superconductors were reported to have a very high upper critical field, B c2 , and low B c2 anisotropy, making them potential candidates for a wide array of future applications [8][9][10][11]. The early results indicate that the global critical current is limited by intergrain currents over the grain boundaries in polycrystalline bulk and wires [12][13][14][15][16][17][18]. Recent experiments revealed that high-angle grain boundary largely deteriorates critical current density J c in Ba(Fe 1-x Co x ) 2 As 2 bicrystals [19,20].…”
mentioning
confidence: 99%